IMPROVING VOCABULARY MASTERY THROUGH DEEP LEARNING APPROACHES WITH VISUAL STRATEGIES (MIND MAPPING) IN GRADE 8. E STUDENTS AT UPT SMP NEGERI 2 GALESONG SELATAN. - Mohd Fakrul Nizam; Aisyah At Thahirah Rukh Umaera; Ummi Khaerati Syam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effectiveness of the Deep Learning approach combined with the Mind Mapping strategy in enhancing the motivation and mastery of basic vocabulary among 8th-grade students at UPT SMP Negeri 2 Galesong Selatan. Limited understanding of essential English vocabulary was identified as a critical issue in the target class. The theoretical framework guiding this research is Allan Paivio’s Dual-Coding Theory, which posits that processing information through both verbal and visual channels significantly improves memory retention. Employing a qualitative case study design, the research utilized pretest and posttest data as the primary evaluation instruments. The results demonstrate a substantial increase in students' vocabulary mastery following the intervention. The average pretest score of 40.0 rose considerably in the posttest, particularly in categories like Body Parts, which showed a remarkable increase from 9 points to 189 points. This improvement confirms that the integration of the Deep Learning approach and Mind Mapping strategy effectively fosters a learning experience that is meaningful, mindful, and joyful (Meaningful, Mindful, Joyful Learning), thereby supporting deeper and more robust vocabulary acquisition.